Optimize The Improvement Of Civic Education Learning Achievement Of 7th Grade Students In Gemah 7 Ambon Middle School Through The Applicationof Discussion And Assignment Methods - Loupatty, Hermelina (Global Science Education Journal, 2019)
This research is a class action research that aims to describe whether there is an increase in student achievement in citizenship education subjects through the implementation of discussion and assignment methods. The subjects in this study were students of class VII-2 SMP Gemah 9 Ambon with a total of 23 students. The research procedure is a series of stages of research from beginning to end. The PTK procedure includes 2 cycles with 2 meetings per cycle. Each cycle consists of four stages as follows: 1) planning; 2) implementing actions; 3) observation and evaluation of actions; and 4) reflection of actions. In this study the data were analyzed to determine the effectiveness of a learning method in teaching and learning activities with a qualitative descriptive approach consisting of 3 stages, namely: 1) Data reduction; 2) data presentation and presentation; and 3) drawing conclusions. This research is said to be successful if students in learning get a value of ?70 (KKM = 70) and or more with an average completeness level of 75% or more. The results of the study show that: (1) The application of the discussion method and the task of learning citizenship education in VII grade students of SMP Gemah 7 Ambon can improve student achievement as seen from the increase in learning achievement tests, namely from the first cycle of 61.6 experiencing an increase in the second cycle to 77.6; (2) The application of the discussion and task method is very effective to be used in the learning of citizenship education in VII grade students of SMP Gemah 7 Ambon in 2018/2019 in odd semester; (3) The steps of applying the discussion method and the task, namely as many as two research cycles are adjusted to the steps in the learning plan so that it can improve the learning achievement of Grade VII students of SMP Gemah 7 Ambon.